'2A‐Like' Signal Sequences Mediating Translational Recoding: A Novel Form of Dual Protein Targeting. (2nd June 2016) - Roulston, Claire; Luke, Garry A.; de Felipe, Pablo; Ruan, Lin; Cope, Jonathan; Nicholson, John; Sukhodub, Andriy; Tilsner, Jens; Ryan, Martin D.
Abstract : We describe '2A‐like' oligopeptide sequences, found as N‐terminal features, which are able to mediate translational recoding – but also to function as a signal sequence. If 2A mediates translational recoding, the 2A signal sequence is synthesized as a discrete translation product separate from the downstream product. If 2A does not mediate translational recoding, the 2A signal sequence is fused to the downstream translation product, functions as a signal sequence and targets the fusion protein to the exocytic pathway. Abstract : We report the initial characterization of an N‐terminal oligopeptide '2A‐like' sequence that is able to function both as a signal sequence and as a translational recoding element. Owing to this translational recoding activity, two forms of nascent polypeptide are synthesized: (i) when 2A‐mediated translational recoding has not occurred: the nascent polypeptide is fused to the 2A‐like N‐terminal signal sequence and the fusion translation product is targeted to the exocytic pathway, and, (ii) a translation product where 2A‐mediated translational recoding has occurred: the 2A‐like signal sequence is synthesized as a separate translation product and, therefore, the nascent (downstream) polypeptide lacks the 2A‐like signal sequence and is localized to the cytoplasm. This type of dual‐functional signal sequence results, therefore, in the partitioning of the translation products between the two sub‐cellular sites and represents a newly described form of dual protein targeting.